2012
DOI: 10.1007/978-1-62703-050-2_16
|View full text |Cite
|
Sign up to set email alerts
|

Non-compartmental Analysis

Abstract: When analyzing pharmacokinetic data, one generally employs either model fitting using nonlinear regression analysis or non-compartmental analysis techniques (NCA). The method one actually employs depends on what is required from the analysis. If the primary requirement is to determine the degree of exposure following administration of a drug (such as AUC), and perhaps the drug's associated pharmacokinetic parameters, such as clearance, elimination half-life, T (max), C (max), et… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
142
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 193 publications
(150 citation statements)
references
References 11 publications
5
142
0
3
Order By: Relevance
“…Plasma samples were added to HEPES buffer (500 mmol/l, pH 7.4) and assayed for fluorescence (496 nm excitation and 520 nm emission, Safire II, Tecan Austria, Grödig, Austria). The exact FITC-inulin dose was calculated from syringe pre to post weight and FITC-inulin clearance was calculated using non-compartmental pharmacokinetic data analysis [30].…”
Section: Methodsmentioning
confidence: 48%
“…Plasma samples were added to HEPES buffer (500 mmol/l, pH 7.4) and assayed for fluorescence (496 nm excitation and 520 nm emission, Safire II, Tecan Austria, Grödig, Austria). The exact FITC-inulin dose was calculated from syringe pre to post weight and FITC-inulin clearance was calculated using non-compartmental pharmacokinetic data analysis [30].…”
Section: Methodsmentioning
confidence: 48%
“…Plasma and homogenized samples were analyzed by means of liquid chromatography with tandem mass spectrometry or highperformance liquid chromatography. The pharmacokinetic parameters of TAS-116 in mice, rats, and dogs were calculated by using noncompartmental methods (25).…”
Section: Histopathologic Examination Of Rat Eye Tissuesmentioning
confidence: 99%
“…In clinical studies, adequate caspofungin peak (11.9 μg/mL) and trough levels (3.7 μg/mL) were maintained during ECMO [72]. However, being more lipophilic, voriconazole was significantly sequestered in the circuit, necessitating higher doses of the drug to maintain adequate trough levels.…”
Section: Antibioticsmentioning
confidence: 40%
“…Unfortunately, PK data in adult patients on ECMO are sparse. Neonatal and animal studies are available but have shown significant variability and unpredictability of antibiotic PK during ECMO [32,35,46,50,[66][67][68][69][70][71][72][73][74][75][76][77][78][79] (Table 1). However, no dosing guidelines exist for this group of patients.…”
Section: Antibioticsmentioning
confidence: 44%